Spontaneous and transgenic rodent models of inflammatory bowel disease - Prattis, Susan (Lab Anim Res, 2015)
Inflammatory Bowel Disease (IBD) is a multifactorial disorder with many different putative influences mediating disease onset, severity, progression and diminution. Spontaneous natural IBD is classically expressed as Crohn's Disease (CD) and Ulcerative Colitis (UC) commonly found in primates; lymphoplasmocytic enteritis, eosinophilic gastritis and colitis, and ulcerative colitis with neuronal hyperplasia in dogs; and colitis in horses. Spontaneous inflammatory bowel disease has been noted in a number of rodent models which differ in genetic strain background, induced mutation, microbiota influences and immunopathogenic pathways. Histological lesions in Crohn's Disease feature noncaseating granulomatous inflammation while UC lesions typically exhibit ulceration, lamina propria inflammatory infiltrates and lack of granuloma development. Intestinal inflammation caused by CD and UC is also associated with increased incidence of intestinal neoplasia. Transgenic murine models have determined underlying etiological influences and appropriate therapeutic targets in IBD. This literature review will discuss current opinion and findings in spontaneous IBD, highlight selected transgenic rodent models of IBD and discuss their respective pathogenic mechanisms. It is very important to provide accommodation of induced putative deficits in activities of daily living and to assess discomfort and pain levels in the face of significant morbidity and/or mortality in these models. Epigenetic, environmental (microbiome, metabolome) and nutritional factors are important in IBD pathogenesis, and evaluating ways in which they influence disease expression represent potential investigative approaches with the greatest potential for new discoveries.